Commercial Drafting and Detailing - Jeﬀeris, Alan (Cengage Learning, 2012)
From site, floor, stair, and roof plans, to framing and foundation plans - take a step-by-step journey through the architectural and structural drawings required in a complete set of commercial plans. Now in its third edition, Commercial Drafting and Detailing provides comprehensive coverage using clear explanations and professional, practical examples. Updates include an all-new chapter devoted to the development and drawing of architectural and structural details, as well as information that reflects the 2009 International Building Code and current Americans with Disabilities Act (ADA) specifications. With these important revisions, and the same clear concise coverage of building materials and skills that characterized previous editions, this book is an ideal resource.